Effect of Fungal and Fungal-Bacterial Tempe-Type Fermentation on the Bioactive Potential of Grass Pea Seeds and Flaxseed Oil Cake Mix - Bożena Stodolak; Maja Grabacka; Anna Starzyńska-Janiszewska; Robert Duliński (International Journal of Food Science)
Tempe is an Indonesian food product traditionally obtained from soybeans through solid-state fermentation with Rhizopus. A variety of substrates can be processed into tempe in the presence of other microorganisms. In this study, grass pea seeds with the addition of flaxseed oil cake (20% w/w) were either fermented using individual mould strains—Rhizopus oryzae, R. oligosporus, and Mucor indicus—or cofermented with the moulds and Lactiplantibacillus plantarum. In the obtained products, the content of dietary fibre, B group vitamins, and the level of peptides and antioxidant potential in aqueous extracts were measured. Moreover, peptides, angiotensin I convertase inhibitor, and antioxidant activity were determined after in vitro digestion. The effect of digestates on the differentiation of enterocytes was also investigated. Fermentation generally resulted in a decrease in the dietary fibre, especially the insoluble fraction (30-50%). The product obtained with R. oryzae was the best source of riboflavin and thiamine among all tested. The fermentation process promoted the accumulation of water-soluble peptides and antioxidant compounds. After in vitro digestion, the largest amount of antioxidant and antiradical compounds was released from tempe obtained with R. oryzae. However, the enrichment of the products with antioxidants resulting from solid-state fermentation did not simply translate into an improvement in antioxidant potential after digestion. Generally, fermentation carried out in the presence of L. plantarum brought positive effects only in the case of R. oligosporus DSM 1964. Digestion products obtained from R. oryzae tempe had a positive effect on the viability of Caco-2 cells differentiated into enterocytes. Interestingly, a higher activity of differentiation markers (alkaline phosphatase and sucrase-isomaltase) was observed under the influence of digestate of R. oryzae and L. plantarum tempe.